Bretton Woods Organisations in a Changing World: A Single Seat for the European Union? - Susanna Cafaro; Francesco Spera (Studia Europejskie)
The European Union represents a new type of regional organisation within the context of international relations. It is also an uncomfortable presence in the internal balances of the so-called “Bretton Woods” organisations – namely, the International Monetary Fund and the World Bank – because it raises several questions and issues. Foremost among these is the legitimacy of expecting that the economic and monetary integration within the EU should be reﬂected in its political and voting representation within these institutions. Secondly, the creation of a single representation of the EU (or the “Euro Area”) encounters numerous legal challenges, both within the framework of EU law and in international law regulating these international organisations. Thirdly, any potential solution must take into account the historical relationships among the EU Member States, as well as their interactions with third countries. However, addressing these problems appears to be an unavoidable knot not only in the process of remodelling the two organisations, but also in updating them to meet the needs of the new millennium. It is a knot which must be untied both by considering the European Union a possible precursor of other regional aggregations that are evolving along the same model in other key regions of the world, and by accepting the EU’s unique characteristics, which to date make it an unparalleled model of state integration. The European Union, as a subject of international law and a potential member of the Bretton Woods institutions, exhibits characteristics that signiﬁcantly deviate from the classical deﬁnition of a state. These distinctive features render the Union, as articulated by its Court of Justice in the landmark 1963 van Gend & Loos case, a “legal order of a new kind in the ﬁeld of international law”. This characterisation positions the Union as a laboratory for the development of innovative solutions, particularly in the realm of external representation, and as an unprecedented phenomenon in the domain of international relations.